녹내장에서 파장가변 빛간섭단층촬영을 이용한 황반부 신경절세포층의 진단력 - 이응석(Eung Suk Lee), 장지호(Jee Ho Chang), 박태관(Tae Kwan Park), 온영훈(Young Hoon Ohn), 박가희(Ka Hee Park) (Daihan angwa haghoi jabji, 2016)
목적: 녹내장 환자에서 파장가변 빛간섭단층촬영(DRI OCT-1, Topcon Co., Tokyo, Japan)을 이용하여 황반부 신경절세포복합체(macular ganglion cell complex, mGCC)와 황반 신경절세포 및 내망상층(macular ganglion cell inner plexiform layer, mGCIPL)의 두께를 분석해 보고 두 방법의 진단력을 확인해 보고자 한다. 대상과 방법: 2014년 8월부터 2015년 7월까지 본원에 내원한 109명 109안을 대상으로 파장가변 빛간섭단층촬영을 이용하여 mGCC와 mGCIPL의 두께를 측정하여 정상군, 초기, 진행된 녹내장군 간의 차이를 확인해 보고, 각각의 진단력, 민감도, 특이도를 구하여 유두주위 망막신경섬유층(circumpapillary retinal nerve fiber layer, cpRNFL) 두께 분석 방법과 비교해 보았다. 결과: 초기와 진행된 녹내장에 대한 area under the curve를 비교해 보았을 때 mGCC는 0.78과 0.99 cpRNFL과 유의한 차이가 없었으나 mGCIPL은 0.70으로 cpRNFL과 초기 녹내장을 진단하는 경우 cpRNFL의 진단력과 유의한 차이를 나타내었고(p=0.018), 녹내장 진단에 대한 민감도와 특이도는 mGCC가 0.95와 0.97, mGCIPL은 0.92와 0.97로 측정되었다. 결론: 두 가지 방법 모두 녹내장을 진단하는 데 있어 높은 민감도와 특이도를 지닌 진단 방법이나, mGCC의 두께 분석 방법이 녹내장의 초기 변화를 감지하는 데 보다 나은 진단력을 가지고 있는 것으로 생각된다. Purpose: To evaluate diagnostic ability of macular ganglion cell complex (mGCC), macular ganglion cell inner plexiform layer (mGCIPL) measurements in glaucoma using swept source deep range imaging optical coherence tomography (DRI OCT-1, Topcon Co., Tokyo, Japan). Methods: From August of 2014 to July of 2015, 109 eyes of 109 subjects were assessed for the average thickness and sectional thickness of both mGCC and mGCIPL to determine whether there exists any significant difference among advanced stage glaucoma group, early stage glaucoma group and normal group in Swept source OCT. Comparisons were also made between the above measurements and circumpapillary retinal nerve fiber layer (cpRNFL) thickness measurements in their diagnostic accuracy, sensitivity, and specificity. Results: The diagnostic ability of mGCC based-mean thickness value (area under the curve [AUC] = 0.78/ 0.99) in detecting early stage glaucoma group as well as advanced stage group was not significantly different from that of cpRNFL thickness measurement. However, there was a significant difference in thickness between mGCIPL (AUC = 0.70) and cpRNFL in early stage glaucoma groups (p = 0.018). The sensitivities and specificities of mGCC were 0.95/0.97, and those of mGCIPL were 0.92/0.97, respectively. Conclusions: The two swept source OCT based methods measuring retinal ganglion cell layer thickness appeared to have a good diagnostic accuracy, high sensitivity and specificity in detecting glaucomatous eyes. Nevertheless, of the two methods, mGCC thickness measurement was more efficient in detecting early glaucomatous changes. KCI Citation Count: 0